VD_FINDINFO Arrêt / 2014 / 348 vom 15. April 2014 - VD Tribunal cantonal (2014)
CURATELLE DE REPRÉSENTATION, CURATELLE DE GESTION, REJET DE LA DEMANDE | 390 al. 1 ch. 1 CC, 394 al. 1 CC, 394 CC, 395 al. 1 CC, 395 CC, 450 CC